Machine learning in the field of dentistry - Li, Hengliang (Nanyang Technological University, 2022)
Oral disease is very common, both old and young will be troubled by it. For more severe and complex cases, dentists often use dental radiographs to diagnose and plan treatment. However, the use of dental radiographs for auxiliary diagnosis can only rely on the experience of doctors, and dental radiographs for the naked eye is complicated, long-time work will lead to human fatigue and misjudgment.